Role of 5-HT1A receptors in the ventral hippocampus in the regulation of anxiety- and panic-related defensive behaviors in rats - Hernandes, Paloma Molina; Batistela, Matheus Fitipaldi; Vilela-Costa, Heloísa Helena; Sant'Ana, Ana Beatriz; Kumpel, Vinicíus Dias [UNESP]; Tirapelle, Mariane Cariati [UNESP]; Bom, Ariela de Oliveira Pedro [UNESP]; de Andrade, Telma Gonçalves Carneiro Spera [UNESP]; Zangrossi, Hélio (Elsevier, 2021)
Changes in 5-HT1A receptor (5-HT1AR)-mediated neurotransmission in the hippocampus have been associated with anxiety, depression and in the mode of action of antidepressant drugs. It has been commonly accepted that whereas the dorsal pole of the hippocampus (DH) is involved in cognitive processing, the ventral pole (VH) is associated with emotional regulation. However, to date, only a few studies have directly addressed the role played by VH 5-HT1ARs in anxiety and panic processing, and their results are conflicting. Here we report that intra-VH administration of the 5-HT1A receptor agonist 8−OH-DPAT, the endogenous agonist serotonin (5-HT), or the standard anxiolytic benzodiazepine midazolam impaired the acquisition of inhibitory avoidance in the elevated T-maze (ETM) of male Wistar rats, indicating an anxiolytic effect. Conversely, local injection of the 5-HT1AR antagonist WAY-100635 caused the opposite effect. These results were equally found in the Vogel conflict test. None of these drugs interfered with locomotor activity in the open-field test, nor did they alter the expression of the escape response in the ETM, a defensive behavior associated with panic. Pre-injection of a sub-effective dose of WAY-100635 in the VH blocked the anxiolytic effect of 5-HT or 8−OH-DPAT in the Vogel test, confirming the involvement of 5-HT1AR for this behavioral effect. The effect in this test was anxiety-selective as none of the drugs affected water consumption or nociception. In conclusion, our results suggest that 5-HT1ARs in the VH play a tonic inhibitory role in anxiety processing. These receptors, however, are not involved in the regulation of panic-related escape behavior.
Keywords: 5-HT1A receptors; Anxiety; Panic; Serotonin; Ventral hippocampus